2010
DOI: 10.2353/ajpath.2010.091267
|View full text |Cite
|
Sign up to set email alerts
|

CNS-Expressed Cathepsin D Prevents Lymphopenia in a Murine Model of Congenital Neuronal Ceroid Lipofuscinosis

Abstract: Deficiency in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 35 publications
4
28
0
Order By: Relevance
“…Thus, it is likely that glial cells in the transduced area and neurons remote from AAV transduction can supply even those neurons that receive a diploid CatD gene deletion with a certain amount of CatD through extracellular secretion (Shevtsova et al, 2010). It was therefore not too surprising that no ceroid accumulation could be detected in ZFN expressing neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is likely that glial cells in the transduced area and neurons remote from AAV transduction can supply even those neurons that receive a diploid CatD gene deletion with a certain amount of CatD through extracellular secretion (Shevtsova et al, 2010). It was therefore not too surprising that no ceroid accumulation could be detected in ZFN expressing neurons.…”
Section: Resultsmentioning
confidence: 99%
“…It will be interesting to investigate whether CD overexpression via adeno-associated viral (AAV) delivery may change the response to MPTP toxicity. In CD homozygous knockout mice, it was shown that exogenous CD delivered to the brain via AAV was able to prevent both neuronal and systemic pathologies associated with CD deficiency, suggesting that CD was transported from the brain to extracranial tissues in the body [18]. A mouse over expressing CD may also more effective in dealing with increases in α-synuclein levels induced by genetic over expression or MPTP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of an AAV vector-mediated expression of cathepsin D (CtsD) in either the brain or visceral organs or both on disease progression was studied in a Ctsd ko mouse [ 52 ]. Treatment of the CNS led to a widespread distribution of CtsD in neurons remote from the injection site, indicating Ctsd secretion from transduced cells and re-uptake of the enzyme by distant cells.…”
Section: Therapeutic Strategies: Preclinical Studies and Clinical Trimentioning
confidence: 99%
“…While enzyme replacement strategies that specifically target the brain have been demonstrated to effectively delay disease progression in various animal models of NCL and recently in patients with CLN2 disease (see above), they will unlikely have a significant impact on the onset and progression of retinal pathology. In fact, an AAV vector-mediated expression of CtsD in the brain of CtsD-deficient mice effectively attenuated neurodegeneration in the brain, but not in the retina [ 52 ]. Similarly, administration of TPP1 to the brain of a canine CLN2 model markedly ameliorated most neurological symptoms [ 16 , 46 ] (see also Sect.…”
Section: Treatment Strategies For Retinal Degeneration and Vision Losmentioning
confidence: 99%